Imperatives of care : women and medicine in colonial Korea - Kim, Sonja M., 1971- (Hawaiʻi studies on Korea., 2019)
In late nineteenth- and early twentieth-century Korea, public health priorities in maternal and infant welfare privileged the new nation's reproductive health and women's responsibility for care work to produce novel organization of services in hospitals and practices in the home. The first monograph on this topic, Imperatives of Care places women and gender at the center of modern medical transformations in Korea. It outlines the professionalization of medicine, nursing, and midwifery, tracing their evolution from new legal and institutional infrastructures in public health and education, and investigates women's experiences as health practitioners and patients, medical activities directed at women's bodies, and the related knowledge and goods produced for and consumed by women. Sonja M. Kim draws on archival sources, some not previously explored, to foreground the ways individual women met challenges posed by uneven developments in medicine, intervened in practices aimed at them, andseized the evolving options that became available to promote their personal, familial, and professional interests. She demonstrates how medicine produced, and in turn was produced by, gendered expectations caught between the Korean reformist agenda, the American Protestant missionary enterprise, and Japanese imperialism.